Políticas y producción audiovisual en la era digital en América Latina (OSAI : Octubre Editorial : CLACSO, 2019)
The new generations naturalize technologies and use them to develop uses and forms of entertainment, communication and business, creating the illusion in consumers of interacting with the gestational process of content. Those who design the technological infrastructure, the devices, the modes of production, distribution and consumption must find in each country the areas to establish social consensus and mechanisms to allow access to the benefits of that better future. Areas that incorporate integration into diversity, strengthening values, cooperative behaviors and creativity. Public policies and the conception of national development models within the framework of regional blocks represent one of the central issues of the CLACSO Working Group "Audiovisual Policies and Production in the Digital Era in Latin America", which we promote from the Observatory of Audiovisual and Infocommunication Sector to discuss in depth key elements of the digital age for the audiovisual sector.We trust that readers will find in this book an opportunity to reflect on these core issues around which humanity and our continent will organize their cultural logics, symbolic and productive to enter the future.